Effects of dietary nucleotides on growth, physiological parameters and antioxidant responses of Juvenile Yellow Catfish Pelteobagrus fulvidraco. (24th August 2015) - Zhao, Hongxia; Cao, Junming; Huang, Yanhua; Zhou, Chuanpeng; Wang, Guoxia; Mo, Wenyan; Chen, Xiaoying
Abstract: The effects of nucleotides on growth, and physiological and antioxidant parameters were evaluated by feeding Pelteobagrus fulvidraco diets supplemented with 0, 0.2, 0.4, 0.6, 1.0 or 1.5 g kg −1 of nucleotides respectively. All nucleotide groups showed higher specific growth rate, feed efficiency, protein efficiency ratio, whole‐body lipid content and serum cholesterol concentrations than the control group, but the significant difference was seen only between fish from the 1.5 g kg −1 nucleotide group and fish from the control group. Whole‐body ash content in fish from the 0.6 g kg −1 nucleotide group, and liver superoxide dismutase and catalase in fish from the 0.4 g kg −1 nucleotide group were significantly higher than those in fish from the control group. Respiratory burst activity was significantly higher in fish from the 0.6, 1.0 and 1.5 g kg −1 nucleotide groups than in fish from the control. This finding was accompanied by lower liver concentrations of thiobarbituric acid‐reacting substances in fish from the same groups compared to those from the control group. The results indicate that dietary nucleotides could improve growth and antioxidant responses in juvenile yellow catfish.